INTERACTION QUALITY DIMENSION TOWARDS SERVICE QUALITY HOSPITAL PUTRAJAYA - Rohaya Roais; Azizi Abu Bakar (Journal of Islamic, Social, Economics and Development, 2020)
Measuring service quality is a better way to know whether they get the good or bad services. That service can measure based on patient or customer respond it is satisfied or not satisfied with service provider. Consequently, the good quality interaction between service provider and patient or customer have needed to get the result as a good service at any facility. Therefore, the study to identify the level of service quality in Hospital Putrajaya based on interaction quality dimension with three sub-dimension attitude and behavior, expertise and work process and the second objective for this study is to examine is it have significant relationship between service quality and interaction quality. So that the management team of Hospital Putrajaya can know what is the level of customer satisfaction of their service provide and how to improve their service quality.